Peran Instruktur Dalam Meningkatkan Hasil Belajar Peserta Didik Program TOEFL dilembaga Kursus English Flash ILC Bojonegoro - Nurmawati, Shofi; Widodo, Widodo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This research aims to analyze and describe the role of instructors at the course institution, as well as the supporting and inhibiting factors in improving the learning outcomes of TOEFL program students at English Flash ILC Bojonegoro. The method used is descriptive qualitative, with data analysis techniques including data collection, data reduction, data presentation, and conclusion drawing. The research results show an improvement in the learning outcomes of TOEFL program students, particularly in cognitive, affective, and psychomotor aspects. In the cognitive aspect, students demonstrated increased understanding and knowledge in solving practice problems, with an average TOEFL score reaching 500. Affectively, students experienced changes in attitudes and values, becoming more confident, expressive, and showing improved speaking abilities, as evidenced by the awards they received. In the psychomotor aspect, students responded positively and were very active in outdoor class activities. The supporting and inhibiting factors of the instructors' role also influenced the improvement of these learning outcomes.